European multinational companies and trade unions in Eastern and East-Central Europe - Martin Myant (European Trade Union Institute (ETUI), 2020)
The fact that multinational companies operate (MNCs) in more than one country can be expected to lead to a weaker bargaining position for labour. However, there are hopes that these companies may, under certain circumstances, transfer good employment practices from their home countries. This theory is investigated for the case of MNCs based in western Europe that invest in the countries of eastern and east-central Europe, where they dominate in several important economic sectors. The established legal and institutional frameworks in those countries give a degree of employment protection, but it is limited. Union recognition by MNCs is quite common, but collective bargaining often provides little beyond existing legal provisions. A series of case studies shows how unions can try to, and sometimes succeed in, getting better results from bargaining. The key conclusion is that international solidarity, contacts and publicity can help unions in host countries, but the ultimate determinant is the determination and organisational strength of employees.
Keywords: 330; Multinational company; labor union; labor relations; East Central Europe; Multinationales Unternehmen; Gewerkschaft; Arbeitsbeziehungen; Ostmitteleuropa